SISA HASIL USAHA KOPERASI DENGAN PENDEKATAN MODAL LUAR, VOLUME USAHA DAN JUMLAH ASET - Gemina, Dwi; Kartini, Tini; Gemini, Pra (Jurnal Akunida, 2021)
Cooperatives are directed as a collective community effort to increase the level of economic prosperity together. The research objective was to analyze the effect of external capital, business volume and total assets on the residual results of operations. The research method used is quantitative with verification. The sample was conducted by purposive sampling based on the criteria of being active in conducting annual member meetings for 10 years. The results show that simultaneously external capital, business volume and total assets have a positive and significant effect on the remaining operating results. Meanwhile, partially, outside capital and total assets have a positive and significant effect on the remaining operating results, business volume has a negative and significant effect on the remaining operating results. Business volume has a negative effect because sales transactions will tend to decrease so that it can also reduce profits or decrease the remaining operating results. Because the smaller the volume of business run by the cooperative, the lower the income from the business.